Sikap terhadap Perilaku Seksual Berisiko pada Siswa Etnik Jawa - Argo Widiharto; Dini Rakhmawati (Philanthropy: Journal of Psychology, 2017)
Adolescence is a period of high risk associated risky sexual behavior. It is quite reasonable because in adolescence began to emerge a strong sex drive due to hormonal changes. Risky sexual behavior is influenced by the attitude. Attitudes toward sexual behavior in adolescents is influenced by several factors including biological, psychological and social or shortened to biopsychosocial. Results of studies with sample sizes of 90, mention of sexual behavior that have been committed by teenagers there are 1.11% of students have agreed attitudes towards risky sexual behavior with 1.11% of students agreed the details of the activity of kissing, amounting to 1.11% of students agreed to the activity of necking and 2.22% of students agreed to the importance of a healthy activity, and no one who had agreed to the activity of intercourse. The small percentage of teen attitudes toward sexual behavior are at risk due to the Javanese culture that is still taboo sexual conversation. Javanese in discussing the sexual use of symbols as smoothing.